2019
DOI: 10.1177/0961000619836706
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Chinese library and information science on outside disciplines: A citation analysis

Abstract: This paper uses citation analysis to measure the intellectual impact of Chinese library and information science on outside disciplines. It analyses 469 journals in disciplines outside the library and information science field containing citations to 20 Chinese library and information science journals from 1996 to 2015. It shows that Chinese library and information science mainly receives citations from related disciplines, such as business and management, communication, and computer science, and that the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 77 publications
(131 reference statements)
1
7
0
Order By: Relevance
“…Based on citation analysis, the researchers analysed the impact of LIS on other disciplines from different perspectives and found that the knowledge in LIS mainly exported to computer science, medicine, business and management, social sciences and other disciplines (Chen et al , 2020; Ding et al , 2021; Meyer and Spencer, 1996; Odell and Gabbard, 2008; Tabatabaei, 2013; Xu, 2016). Meyer and Spencer (1996) analysed the citations to 24 library science (LS) journals from 1972 to 1994, and the results suggested that the disciplines citing LS papers included computer science, social sciences, medicine, psychology and general sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Based on citation analysis, the researchers analysed the impact of LIS on other disciplines from different perspectives and found that the knowledge in LIS mainly exported to computer science, medicine, business and management, social sciences and other disciplines (Chen et al , 2020; Ding et al , 2021; Meyer and Spencer, 1996; Odell and Gabbard, 2008; Tabatabaei, 2013; Xu, 2016). Meyer and Spencer (1996) analysed the citations to 24 library science (LS) journals from 1972 to 1994, and the results suggested that the disciplines citing LS papers included computer science, social sciences, medicine, psychology and general sciences.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Radicchi et al (2008) analyzed the universality of citation distributions based on the full text in a single publication, and they only assessed several disciplines using the numbers of citations (Radicchi, Fortunato and Castellano, 2008). Exploring the distribution of references from disciplines in academic papers can help to better understand the influences of different disciplines in research (Chen et al, 2019). Steele and Stier (2000) researched Environmental Science through the study of the diversity of the disciplines of citations.…”
Section: Distributions Of the References From Different Disciplinesmentioning
confidence: 99%
“…Therefore, many scholars seek to better understand the research status and influence of different disciplines based on academic papers and the location of references in them (Zhuge, 2006;Hassan and Haddawy, 2015;Wang and Zhang, 2018). And some use bibliographic information to explore the performance of different disciplines in citing and cited works (Steele and Stier, 2000;Chen et al, 2018;Chen et al, 2019). However, these studies mainly use traditional citation analysis and focus on one discipline.…”
Section: Introductionmentioning
confidence: 99%
“…The argument regarding the identity of LIS has also been raised by Chinese scholars (Ma, 2013; Zhao, 2013), although most Chinese scholars believe that LIS is an interdisciplinary discipline rather than three independent fields (Chen et al, 2019; Li et al, 2018; Wang and Zhao, 2015). Dissertation research topics have also been used to investigate the evolution of research topics within LIS in China, as well as its interdisciplinary identity.…”
Section: Literature Reviewmentioning
confidence: 99%